Vulnerable Populations: Comparison of Characteristics of Adolescent Inpatients with Substance Use Disorder and a History of Child Maltreatment to Inpatients without a History of Child Maltreatment: A Retrospective Chart Review - Michèle Preyde; Shrenik Parekh; John Heintzman (MDPI AG, 2022)
Background: Adolescent inpatients with substance use disorder (SUD) and a history of child maltreatment (CM) present a vulnerable population at considerable risk of poor health and social outcomes. The aims of this study were to explore the proportion of adolescent inpatients with SUD and a history of CM and to compare these patients to inpatients with SUD and no history of CM. Methods: In this retrospective chart review, we explored adolescent patients who were consecutively admitted to a regional child and adolescent inpatient unit for psychiatric care and met DSM (5th ed) criteria for SUD. A standardized form was created and used to extract clinical information and psychosocial histories. Results: From 1 September 2019 to 28 February 2020, 126 adolescents were admitted with SUD, and for 80 (63.3%) patients, a history of CM was recorded in the medical charts. Patients with a history of CM were significantly more likely to be female (p = 0.02), have longer lengths of stay (p = 0.04), to be readmitted (p = 0.03), be diagnosed with trauma/stress-related (p = 0.04) and eating disorders (p = 0.05), to have a parent with a mental illness (p = 0.01), experienced physical (p < 0.01) and sexual (p < 0.01) assaults and homelessness (p < 0.01), and to engage in self-harming behaviors (p < 0.01) than inpatients with SUD but no history of CM. Conclusions: Almost two-thirds of adolescent inpatients with an SUD reported a history of CM. Addressing their specific clinical and psychosocial vulnerabilities through comprehensive treatment and discharge plans may reduce readmission and improve quality of life.